2021
DOI: 10.3389/fpubh.2021.661345
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to Holiday Club Food Provision to Alleviate Food Insecurity During the Covid-19 Pandemic

Abstract: Holiday clubs play a pivotal role in providing food and vital enrichment opportunities to alleviate food insecurity among children during the school holidays (holiday hunger). The need for these opportunities increased substantially for families throughout 2020, as food insecurity quadrupled in the UK during the Covid-19 pandemic. In this qualitative study, holiday club staff from England and Wales reflected on the adaptations they implemented in order to maintain food supplies and food-related enrichment acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…A previous HAF Programme evaluation reported that organizing the delivery of the Programme with Providers was more difficult for Co-ordinators when the Providers were ‘new' and unknown to the Co-ordinators prior to the Programme ( 14 ). During the COVID-19 pandemic, partnership working had been identified by Holiday Clubs as an important process to adapt delivery and maintain resilience to ensure vulnerable communities continued to receive support ( 22 ). Partnership working within the current evaluation, was often the result of collaboration on previous projects however, it also included contacting previously unknown Holiday Club Providers and asking if they needed any additional assistance in preparing for the HAF Programme.…”
Section: Discussionmentioning
confidence: 99%
“…A previous HAF Programme evaluation reported that organizing the delivery of the Programme with Providers was more difficult for Co-ordinators when the Providers were ‘new' and unknown to the Co-ordinators prior to the Programme ( 14 ). During the COVID-19 pandemic, partnership working had been identified by Holiday Clubs as an important process to adapt delivery and maintain resilience to ensure vulnerable communities continued to receive support ( 22 ). Partnership working within the current evaluation, was often the result of collaboration on previous projects however, it also included contacting previously unknown Holiday Club Providers and asking if they needed any additional assistance in preparing for the HAF Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Following de-identification, transcripts were uploaded to NVivo version 12 software. To analyse data, a reflexive thematic analysis was used, in line with the principles of Bayes, Holley, Haycraft, and Mason (2021 ; 2021). This process began with two research team members (TM and HA) independently reading and coding three transcripts and then discussing any codes or emerging themes of potential significance to the research objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, academics agree that greater resilience to a crisis is related to a higher level of sustainability [40], and it is strategically important [41]. The result of limited resilience capacities can be observed in various studies examining diverse industries during COVID-19 [42][43][44].…”
Section: Definition Of Organisational Resiliencementioning
confidence: 99%